Using bioinformatics technology to mine the expression of serum exosomal miRNA in patients with traumatic brain injury - Huang, Xintao; Xu, Xinjuan; Wang, Ce; Wang, Yi; Yang, Yajun; Yao, Tianle; Bai, Rui; Pei, Xile; Bai, Feirong; Li, Panpan (Frontiers in Neuroscience, 2023)
Introduction Traumatic brain injury (TBI) is considered the most common traumatic neurological disease, is associated with high mortality and long-term complications, and is a global public health issue. However, there has been little progress in serum markers for TBI research. Therefore, there is an urgent need for biomarkers that can sufficiently function in TBI diagnosis and evaluation. Methods Exosomal microRNA (ExomiR), a stable circulating marker in the serum, has aroused widespread interest among researchers. To explore the level of serum ExomiR after TBI, we quantified ExomiR expression levels in serum exosomes extracted from patients with TBI using next-generation sequencing (NGS) and explored potential biomarkers using bioinformatics screening. Results Compared with the control group, there were 245 ExomiR (136 up-regulated and 109 down-regulated) in the serum of the TBI group that changed significantly. We observed serum ExomiRs expression profiles associated with neurovascular remodeling, the integrity of the blood-brain barrier, neuroinflammation, and a cascade of secondary injury, including eight up-regulated ExomiRs (ExomiR-124-3p, ExomiR-137-3p, ExomiR-9-3p, ExomiR-133a-5p, ExomiR-204-3p, ExomiR-519a-5p, ExomiR-4732-5p, and ExomiR-206) and 2 down-regulated ExomiR (ExomiR-21-3p and ExomiR-199a-5). Discussion The results revealed that serum ExomiRs might become a new research direction and breakthrough for the diagnosis and pathophysiological treatment of patients with TBI.